2022
DOI: 10.1186/s12936-021-04036-y
|View full text |Cite
|
Sign up to set email alerts
|

Presence and potential distribution of malaria-infected New World primates of Costa Rica

Abstract: Background In South and Central America, Plasmodium malariae/Plasmodium brasilianum, Plasmodium vivax, Plasmodium simium, and Plasmodium falciparum has been reported in New World primates (NWP). Specifically in Costa Rica, the presence of monkeys positive to P. malariae/P brasilianum has been identified in both captivity and in the wild. The aim of the present study was to determine the presence of P. brasilianum, P. falciparum, and P. vivax, and the potential distribution of these parasites-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…Mico 156 Brazil 156 Interstitial pneumonia 156 RT-PCR 156 ; IHC 156 Hemozoin pigment intracytoplasmic in macrophages at red pulp from the spleen 3 NP 23,25,33,41,64,145,169 HP 3 , Blood-smears cytology 3,25,64 , Blood-PCR 3,23,25,33,41,64 , Stool-PCR 79,169 , Nested-PCR 145 , IFA 64 Entamoeba Alouatta 219 Mexico 219 NP 219 FPE 219 , PCR 219…”
Section: Sars-cov-2mentioning
confidence: 99%
See 3 more Smart Citations
“…Mico 156 Brazil 156 Interstitial pneumonia 156 RT-PCR 156 ; IHC 156 Hemozoin pigment intracytoplasmic in macrophages at red pulp from the spleen 3 NP 23,25,33,41,64,145,169 HP 3 , Blood-smears cytology 3,25,64 , Blood-PCR 3,23,25,33,41,64 , Stool-PCR 79,169 , Nested-PCR 145 , IFA 64 Entamoeba Alouatta 219 Mexico 219 NP 219 FPE 219 , PCR 219…”
Section: Sars-cov-2mentioning
confidence: 99%
“…Free-ranging howler monkeys (A. guariba clamitans) are considered de main reservoir of malaria in the Atlantic Forest. Studies using blood and stool PCR have shown high prevalence (30 to 70%) of Plasmodium in free-ranging populations from fragmented and peri-urbanized areas, in some cases coinciding with human malarian outbreaks (3,33,41,145,169). Animals were infected with P. simium, P. falciparuim, and P. brazilianum, and at hematological and biochemical analysis the infected animals presented lymphocytosis, hypoalbuminemia, and high levels of ALT, that were even higher in mixed infections (3,145,169).…”
Section: Plasmodium Sppmentioning
confidence: 99%
See 2 more Smart Citations
“…The black-box approach integrates across the entire transmission system, assuming that the final distribution of disease cases summarizes all biotic interactions involved in the transmission [44,61]. This approach is useful when transmission dynamics are poorly understood and data are limited [44,66], as happens for many VBDs (e.g., [67][68][69]). However, the black-box oversimplification in such intricate transmission systems may be perilous, as it neglects the ecological requirements of the individual component species [55,66].…”
mentioning
confidence: 99%